Prescribed Opioid Difficulties, Depression, and Opioid Dose Among Chronic Opioid Therapy Patients - Merrill, Joseph O. (2012)
BACKGROUND: Chronic opioid therapy has increased dramatically, as have complications related to prescription opioids. Little is known about the problems and concerns attributed to opioids by patients receiving different opioid doses. METHODS: We surveyed 1883 patients who were receiving chronic opioid therapy for chronic non-cancer pain. Opioid regimen characteristics were ascertained from electronic pharmacy records. Patient-reported opioid-related problems and concerns were measured using the Prescription Opioid Difficulties Scale. Depression was assessed with the Patient Health Questionnaire. RESULTS: Patients prescribed higher opioid doses reported modestly higher pain intensity and pain impact. After adjustment, patients on higher doses attributed higher levels of psychosocial problems and control concerns to prescribed opioids (p<.0001). They also had higher levels of depression and were more likely to meet criteria for clinical depression. Over 60% of patients receiving 120+ mg daily (morphine equivalent) were clinically depressed, a 2.6-fold higher risk (95% CI of 1.5 to 4.4) than patients on low dose regimens (< 20 mg daily). CONCLUSIONS: Higher opioid doses were associated with somewhat higher pain severity and higher levels of patient-reported opioid-related psychosocial problems, control concerns, and depression. These findings may result from patient selection for high dose therapy or problems caused by higher dose opioids.